Penguatan Akses Pasar Produk Aren melalui Pendampingan Pemasaran Berbasis Event Car Free Day (CFD) pada KTH Desa Giri Madia - Sakinah; Ida Ayu Widhiantari; Aisah Dwi Lestari; Salma; Tiara Kurnia Sari Dewi; Dygta Tri Juandti; Muh. Fajar Islam; M. Hairul Azmi; M. Khairul Hasbi; M. Khaerul Rizal (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Giri Madia Village, Lingsar District, West Lombok Regency, has the potential for non-timber forest products in the form of sugar palm, which is managed by the Giri Madia Forest Farmers Group (KTH) under the Community Forestry (HKm) scheme. Although processed sugar palm products such as palm sugar, palm sugar, liquid palm sugar, and other derivative products have high economic value, their development still faces limitations in the marketing aspect. This community service activity aims to strengthen market access for sugar palm products through event-based marketing assistance. The implementation method is carried out in stages, including preparation, implementation, and evaluation stages. Marketing assistance is carried out through participation in several public events, namely Car Free Day (CFD) on Jalan Udayana, the opening bazaar of the 126th TNI Manunggal Membangun Desa (TMMD) at Dasan Griya, and Sunday Morning activities at the West Lombok Regent's office area. The results of the activities show that event-based marketing is able to increase product visibility, expand consumer reach, and increase the capacity and confidence of KTH members in marketing sugar palm products. In addition, the diversification of processed sugar palm products also increases the product's appeal in the market. This activity is expected to become a sustainable marketing strategy to support the economic empowerment of the Giri Madia Village community based on local potential.